2017
DOI: 10.1080/10826084.2016.1264971
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and Substance Use Disorder Determinants of HIV Sexual Risk Behavior in Men and Women in Outpatient Drug Treatment in the NIDA National Drug Abuse Treatment Clinical Trials Network

Abstract: BACKGROUND Sexual risk behavior is now the primary vector of HIV transmission among substance users in the United States with gender as a crucial moderator of risk behavior. OBJECTIVES The purpose of this study was to examine gender differences in factors (age, race/ethnicity, education) that predict main-partner unprotected sexual occasions (USO) using the unique platform of two parallel NIDA National Drug Abuse Treatment Clinical Trials Network gender-specific safer sex intervention trials. METHODS Basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Familial studies have reported an increased risk of addiction in persons with a genetic predisposition [ 15 , 16 ], but this increased vulnerability is subject to the interplay between gene and environment. Sociodemographic factors such as peer pressure, unemployment, and geographical location can influence the onset and outcome of substance abuse [ 17 ]. Psychological factors predicting a person’s vulnerability to substance abuse include a history of trauma, high psychopathology of anxiety, and depression [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Familial studies have reported an increased risk of addiction in persons with a genetic predisposition [ 15 , 16 ], but this increased vulnerability is subject to the interplay between gene and environment. Sociodemographic factors such as peer pressure, unemployment, and geographical location can influence the onset and outcome of substance abuse [ 17 ]. Psychological factors predicting a person’s vulnerability to substance abuse include a history of trauma, high psychopathology of anxiety, and depression [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Four donors had known risk factors for HHV‐8 infection; MSM (Donors 2 and 6) or IDU (Donors 4 and 5). Donors 1 and 3 had probable risk factors for HHV‐8 infection as regular users of methamphetamine (also heroin and cocaine for Donor 3), which is associated with high‐risk sexual behaviors (trading sex for drugs and money) 14,15 and IDU 16 . Organs from 6 donors were transplanted into 22 recipients (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, donor history questionnaires can have incomplete information 25 . Donor 1 was noted to be sexually active with unknown gender preference, which may imply MSM behavior, and was a frequent user of methamphetamine, which is associated with high‐risk sexual behavior 14,15 and IDU 16 . Donor 3 was reported to inhale methamphetamine, cocaine, and heroin, which are associated with high‐risk sexual behavior 14,15 and IDU 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol intoxication and drug use lead the user to increase the probability of doing or getting involved in something potentially harmful (19) , such as drunk driving, violent behaviors, and crimes (20) , or negligent behavior (sexual, for example) (21) . About activities, they can increase the probability of accidents (22) , leading to an increased risk of injuries and traumas (17) .…”
Section: Discussionmentioning
confidence: 99%